2016
DOI: 10.1063/1.4955085
|View full text |Cite
|
Sign up to set email alerts
|

Capillary-inertial colloidal catapults upon drop coalescence

Abstract: Surface energy released upon drop coalescence is known to power the self-propelled jumping of liquid droplets on superhydrophobic solid surfaces, and the jumping droplets can additionally carry colloidal payloads toward self-cleaning. Here, we show that drop coalescence on a spherical particle leads to self-propelled launching of the particle from virtually any solid surface. The main prerequisite is an intermediate wettability of the particle, such that the momentum from the capillary-inertial drop coalescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In addition to liquid-mediated phenomena, the developed platform presented here lends itself to studies of self-cleaning, , where coalescence-induced droplet jumping can remove solid particles from the surface. On the vapor side, recent numerical studies have shown the importance of the surrounding vapor/gas density and flow field on the coalescence and detachment process .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to liquid-mediated phenomena, the developed platform presented here lends itself to studies of self-cleaning, , where coalescence-induced droplet jumping can remove solid particles from the surface. On the vapor side, recent numerical studies have shown the importance of the surrounding vapor/gas density and flow field on the coalescence and detachment process .…”
Section: Discussionmentioning
confidence: 99%
“…Such a dominance gives rise tô ' Ã T 1, which is impressive considering that the capillaryinertial velocity is about the best attainable in self-propelled motion powered by surface energy. The effectiveness will be significantly reduced if the drop coalescence is symmetric instead, as shown in a related capillary -inertial colloidal catapult where the merged drop has a predominantly oscillatory motion [31].…”
Section: Role Of Asymmetric Coalescencementioning
confidence: 99%
“…ballistic launching systems for small projectiles [32 -34] and self-cleaning systems for colloidal contaminants [31,35,36]. Competing interests.…”
mentioning
confidence: 99%
“…When two microdroplets coalesce on superhydrophobic surfaces (SHSs), the coalesced droplet will jump out of the plane spontaneously . This jumping phenomenon is observed not only on natural materials, such as lotus leaf, gecko skin, and cicada wings, but also on fabricated SHSs with nanoscale or hierarchical structures. The coalescence-induced droplet jumping has showed its great potential in thermal management, , self-cleaning surfaces, anti-icing surfaces, condensation heat transfer enhancement, and energy harvest …”
Section: Introductionmentioning
confidence: 99%